Experimental Painting and Painting Theories in Colonial Hong Kong (1940-1980): Reflection on Cultural Identity - K.W. Man, Eva (Filozofski vestnik, 2016)
The article provides a brief description of the fabulous history of painting and painting theories in the rapidly developing Hong Kong from 1940 to 1980 by highlighting the work and aesthetics of several representative local Chinese painters and art institutions. This outline of history reflects a search for cultural identity and the different attitudes among Chinese painters who struggled between modernized and Western influences in art and their Chinese tradition. Comparison is made with the attitudes of the younger generation in the 80’s, which reflects the capitalist influences on the search for an artistic identity. Finally, art and cultural theories in a contemporary post-colonial discourse are critically examined in view of their application to the present situation in Hong Kong.